2019
DOI: 10.15295/bmij.v7i5.1290
|View full text |Cite
|
Sign up to set email alerts
|

Ki̇şi̇-Çevre Uyumunun Farkli Kavramsal Yaklaşimlar Açisindan Çok Düzeyli̇ Ölçümü; Hemşi̇releri̇n Uyum Algilari İle Çalişma Tutum Ve Davranişlari Arasindaki̇ İli̇şki̇leri̇n İncelenmesi̇

Abstract: Kişi-çevre uyumu, bireyin bir veya birden çok özniteliği ve içerisinde bulunduğu ortamın özelliklerini yansıtan ortak değerlerin uyumluluk durumu olarak tanımlamaktadır. Uyumun işlevsel hale getirilmesinde bütüncül yaklaşımların benimsendiği ve farklı unsurların etkilerinin bir arada incelendiği araştırmalar, kişi-çevre uyumu literatürüne sağladığı katkılar açısından ihtiyaç duyulan nitelikte çalışmalar olarak değerlendirilmektedir. Yürütülen araştırmada, uyum alanında farklı kavramsallaştırma yaklaşımları ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the literature, person-supervisor fit was mostly examined as a component of the person-environment fit variable and in multi-level studies, it is seen that person-supervisor fit is often examined together with person-organization fit research. According to the researchers, person-supervisor fit and person-organization fit exist today as two interconnected types of fit (Tatlı & Çakmak, 2019). In many studies, it is revealed that there was a positive and significant relationship between organizational identification and person-organization fit (Akbaş & Çetin, 2015;Demir et al, 2019;Sökmen & Bıyık, 2016).…”
Section: 6mediating Role Of Organizational Dna Between the Relationsh...mentioning
confidence: 99%
“…In the literature, person-supervisor fit was mostly examined as a component of the person-environment fit variable and in multi-level studies, it is seen that person-supervisor fit is often examined together with person-organization fit research. According to the researchers, person-supervisor fit and person-organization fit exist today as two interconnected types of fit (Tatlı & Çakmak, 2019). In many studies, it is revealed that there was a positive and significant relationship between organizational identification and person-organization fit (Akbaş & Çetin, 2015;Demir et al, 2019;Sökmen & Bıyık, 2016).…”
Section: 6mediating Role Of Organizational Dna Between the Relationsh...mentioning
confidence: 99%